Effectiveness of Transdiagnostic Cognitive Behaviour Therapy for Anxiety and Depression in Adults: A Systematic Review and Meta-analysis. Issue 6 (15th June 2016) - Andersen, Philip; Toner, Paul; Bland, Martin; McMillan, Dean
Abstract : Background: Transdiagnostic Cognitive Behaviour Therapy (CBT) seeks to identify core cognitive-behavioural processes hypothesized to be important across a range of disorders and to develop a treatment that targets these. This contrasts with standard CBT approaches that are disorder-specific. Proponents of transdiagnostic CBT suggest that it may offer advantages over disorder-specific CBT, but little is known about the effectiveness of this approach.Aims: The review aimed to summarize trial-based clinical and cost-effectiveness data on transdiagnostic CBT for anxiety and depression.Method: A systematic review of electronic databases, including peer-reviewed and grey literature sources, was conducted ( n = 1167 unique citations).Results: Eight trials were eligible for inclusion in the review. There was evidence of an effect for transdiagnostic CBT when compared to a control condition. There were no differences between transdiagnostic CBT and active treatments in two studies. We found no evidence of cost-effectiveness data.Conclusions: Quality assessment of the primary studies indicated a number of methodological concerns that may serve to inflate the observed effects of transdiagnostic approaches. Although there are positive signs of the value of transdiagnostic CBT, there is as yet insufficient evidence to recommend its use in place of disorder-specific CBT.